2021
DOI: 10.1021/acs.jproteome.1c00054
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis Identifies Prolonged Disturbances in Pathways Related to Cholesterol Metabolism and Myocardium Function in the COVID-19 Recovery Stage

Abstract: The COVID-19 pandemic has become a worldwide health crisis. So far, most studies have focused on the epidemiology and pathogenesis of this infectious disease. Little attention has been given to the disease sequelae in patients recovering from COVID-19, and nothing is known about the mechanisms underlying these sequelae. Herein, we profiled the serum proteome of a cohort of COVID-19 patients in the disease onset and recovery stages. Based on the close integration of our proteomic analysis with clinical data, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
2
23
0
Order By: Relevance
“…Chen Y. et al [ 44 ] profiled via DIA-MS the serum proteome of 10 moderate and 6 severe COVID-19 patients (and 10 healthy controls) during the disease and at recovery stages. A first analysis was performed to explain the long-term disturbances affecting subjects also after recovery.…”
Section: Proteomics Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Chen Y. et al [ 44 ] profiled via DIA-MS the serum proteome of 10 moderate and 6 severe COVID-19 patients (and 10 healthy controls) during the disease and at recovery stages. A first analysis was performed to explain the long-term disturbances affecting subjects also after recovery.…”
Section: Proteomics Of Covid-19mentioning
confidence: 99%
“… The main findings obtained from the review of proteomics studies are summarized. In particular, the results from plasma [ 34 , 35 , 36 , 38 , 39 , 40 , 41 , 42 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ] and serum [ 43 , 44 , 45 , 46 , 47 , 83 , 86 ] studies were merged to identify the common proteins (top) that should represent the proteome signature of COVID-19. These protein entries were analyzed and clustered using STRING version 11.5, revealing the formation of three main clusters (bottom).…”
Section: Figurementioning
confidence: 99%
“…Evidence suggests substantial alterations in metabolomic and proteomic profiles, oral and gut microbiome, and lipid metabolism following SARS-CoV-2 infection in previously healthy individuals, 1 , 2 , 3 , 4 with some of these abnormalities persisting even in the post-acute stage (ie, >30 days after SARS-CoV-2 infection) of COVID-19. 5 Although total cholesterol, LDL cholesterol, and HDL cholesterol are often reduced during the acute phase of SARS-CoV-2 infection, emerging evidence from small observational studies with short follow-ups (of up to 6 months) suggest increased risk of dyslipidaemia in the post-acute phase of COVID-19. 4 , 5 , 6 , 7 , 8 , 9 A study of 501 young adults (aged 18–30 days) of the Swiss Armed Forces showed that compared with non-infected controls, those with COVID-19 had a higher blood cholesterol and LDL concentrations 180 days after their first positive PCR test.…”
Section: Introductionmentioning
confidence: 99%
“…Retesting of NPS samples to control the rate of false-negatives would be advisable, nevertheless, it was not possible because the molecular detection of SARS-CoV-2 on NPS samples was performed in the frame of routine laboratory diagnosis and we do not have access to these samples. Despite a negative RT-qPCR result, the persistence of virus molecules or infection-related proteins would likely occur, and sustainability of serological inflammatory markers several days or weeks after patients recovery was reported [51,52]. These long-term protein dysregulations could perturb ML classification.…”
Section: Discussionmentioning
confidence: 99%